Blog quality model - Muhammad Zain, Zuhaira; Abd Ghani, Abdul Azim; Abdullah, Rusli; Atan, Rodziah; Yaakob, Razali (Inderscience Publishers, 2013)
Breakthroughs in technology are making the internet an ever-growing phenomenon, and we have witnessed an enormous growth of blogs in the blogosphere. However, the blogosphere has been crippled by disorganised and uncontrolled growth, and many blogs are of poor quality. Development domains, such as software engineering, website engineering, and information systems, have provided accepted models for the assessment of the quality of their products. However, to the best of our knowledge, there appears to be no standard model for the assessment of blog quality. In this paper, we propose a blog quality model as a guide for bloggers at large, with a set of 49 criteria grouped into 11 families of features that are relevant to blog quality. This model has been constructed by determining a set of criteria from a review of the relevant literature and blogs and then measuring the acceptability of these criteria by means of questionnaire surveys sent to sample populations of blog readers.